Empowering communities to create change: hybridizing appreciative inquiry and world café to inform asset-based community development - Lavey, Devin (Kansas State University, 2023)
As we engage and evaluate communities in the hopes of building upon their assets, it is important that we encourage participation by community members through various engagement methods. This research aims to explore how Asset-Based Community Development is informed by community engagement through the processes of Appreciative Inquiry and World Café. The research was conducted during the summer of 2022 by Minneapolis Health Department Healthy Living Initiative members at the Minneapolis Public Housing Authority property of Glendale Townhomes. By evaluating the community engagement model of Appreciative Inquiry to inform the content of the World Café discussion, I conclude that Asset-Based Community Development can be greatly informed to create change.
Keywords: Community engagement; World café; Appreciative inquiry; Asset based community development